Structure Analysis of Cast Iron for Dry Clutch of Amphibious Vehicle - Hassan, Muhammad Zahir; Md Isa, Muhammad Fahmi; Razali, Muhammad Razil; Abdul Manaf, Muhammad Zaidan (Seventh Sense Research Group, 2013)
This paper investigates the structure analysis of cast iron for dry clutch disc of amphibious vehicle. The main focus that needs to be considered is the torque produced from the engine. Optimum parameters must be justified in order to confirm the clutch disc is high durability, high reliability, and minimum in weight. Finite element analysis is use to predict the maximum stress can be apply to the disc. The fabrication process is conduct using a conventional milling machine.